Toward developing Ti alloys with high fatigue crack growth resistance by additive manufacturing. (1st January 2023) - Wang, F.; Lei, L.M.; Fu, X.; Shi, L.; Luo, X.M.; Song, Z.M.; Zhang, G.P.
Highlights: Fatigue crack growth behaviors were investigated for TA19 alloy fabricated by laser metal deposition. The α lath width and the angle between the α lath and the applied stress direction affect the near-threshold fatigue crack growth rate. Columnar prior-β grain growth direction and grain boundaries can affect fatigue crack growth rate in the Paris regime. Scanning strategies and process parameters to additively manufacture Ti alloys with high fatigue damage tolerance are suggested. Abstract: Fatigue crack growth behaviors were investigated by three-point bending tests for TA19 alloy fabricated by laser metal deposition and four kinds of heat-treated samples. The crack growth resistance of the TA19 samples in the near-threshold regime and Paris regime was evaluated through the experimental characterization and theoretical analysis of the interaction between fatigue crack and α/β phase interface, columnar prior-β grain boundary and colony boundary. The results show that in the near-threshold regime, the fatigue crack propagation threshold and resistance increase with the increase of widths of lamellar αp phases and colonies, and the decrease of the number of α laths with an angle ( φ ) relative to the applied stress direction ranging from 75° to 90°. In the Paris regime, the fatigue cracking path can be deflected at colony boundaries or columnar prior-β grain boundaries. The larger the deflection angle, the more tortuous the cracking path and the lower the fatigue crack growth rate. The angle ( γ ) of the columnar prior-β grain growth direction relative to the build direction affects not only φ of different α variants, but also the fatigue cracking path deflection angle ( θij ) at columnar prior-β grain boundaries. An optimal combination of γ  = 0°-15°-0°-15° for several adjacent columnar prior-β grains is derived from the theoretical analysis, and that can effectively avoid φ being in the range from 75° to 90° and make θij as large as possible. Such findings provide a guide for the selection of scanning strategies and process parameters to additively manufacture Ti alloys with high fatigue damage tolerance. Graphical abstract: Image, graphical abstract